Abdominal wall closure in the presence of sepsis (acute abdomen): role of negative suction - P. B., Thrishuli; E., Pavan Kumar (International Surgery Journal, 2018)
Background: To compare and find out the best method of abdominal wall closure in cases peritonitis between subcutaneous negative suction drainage tube and conventional primary skin and subcutaneous closure. Methods: From September 2015 to September 2017, 100 patients who presented at the emergency department with acute abdominal pain and operated for the same, with features s/o peritonitis were enrolled into the study. 50 of them were managed with subcutaneous negative suction drainage tube during abdominal wall closure (Group A). 50 other patients underwent conventional method of abdominal wall closure (Group B). On table pus c/s was sent for all 100 cases. The surgical wound was observed for signs of infection. Any seropurulent collection from the drain or any discharge from the wound was sent for c/s and the results of which were compared with the results of on table pus c/s. If wound dehiscence was noted, secondary suturing was done after the wound healed. The duration of suction drain placement and stay in the hospital were noted in all cases. The results were analyzed with Chi-square test and Student t test (unpaired) and p values were calculated. A p value of less than 0.05 was considered significant. Results: The incidence of SSI was significantly less in Group A (20%) than in Group B (64%). Similarly, wound dehiscence occurred in 30% of SSI cases in Group A as against 87.1% of SSI cases in Group B, the difference of which was statistically significant. The mean duration of hospital stay was significantly less when subcutaneous suction drain was placed (8 days). Conclusions: Subcutaneous suction drainage tube is an effective method of abdominal wall closure in cases of peritonitis when compared to conventional primary skin closure as it significantly reduces the incidence of SSI, wound dehiscence, wound secondary suturing and duration of hospital stay.